Experimental Study of Pipes Shape Effect on Noise Reduction - Muna S. Kassim; Ammar Fadhil Hussein Al-Maliki (Wasit Journal of Engineering Sciences)
Internal combustion engine is a major source of noise pollution. These engines are used for various purposes such as, in power plants, automobiles, locomotives, and in various manufacturing machineries. The noise is caused by two reasons; the first reason is the pulses which created when the burst of high pressure gas suddenly enters the exhaust system, while the second reason is the friction of various parts of the engine where the exhaust noise is the most dominant. The limitation of the noise caused by the exhaust system is accomplished by the use of silencers and mufflers. The aim of this study is the reduction of the noise by changing its inlet and outlet pipe length and shape. Also the losses in noise for different length and shapes have been investigated experimentally. The results show that the corrugated pipe is preferable for noise reduction.